equação 9x-3=6×+4 1 grau
Soluções para a tarefa
Respondido por
1
Isola o X:
![9x - 6x = 4 + 3 \\ 3x = 7 \\ x = \frac{7}{3} 9x - 6x = 4 + 3 \\ 3x = 7 \\ x = \frac{7}{3}](https://tex.z-dn.net/?f=9x+-+6x+%3D+4+%2B+3+%5C%5C+3x+%3D+7+%5C%5C+x+%3D++%5Cfrac%7B7%7D%7B3%7D+)
Respondido por
1
Resposta:9x-3=6x+41
Passa o x < subtraindo
e o tres para la > somando
9x-6x=41+3
15x=44
^^
Explicação passo-a-passo:
s
Perguntas interessantes
Ed. Técnica,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás